Using chills-inducing music to augment self-transcendence, emotional breakthrough, and psychological insight during mindfulness and loving kindness meditation - Christov-Moore, Leonardo; Schoeller, Felix; Von Guttenberg, Mathilda; Durinski, Tiffany; Walder, Mordechai; Jain, Felipe A.; Iacoboni, Marco; Reggente, Nicco (Frontiers in Psychology, 2026)
IntroductionNon-pharmacologically induced altered states of consciousness that promote mental health and wellbeing are a growing focus of clinical and basic research. Previous work has revealed the mood-augmenting, belief-altering, and self-transcendent effects of aesthetic-chills-inducing audiovisual stimulation. The current study investigated how a guided loving kindness meditation (LKM) combined with uplifting, chills-inducing music (henceforth: chills-augmented) affected participants’ mood, self-transcendence (ST), psychological insight, and emotional breakthrough.MethodsWe conducted a randomized, controlled online study (n = 398) using a 2 × 2 design comparing a validated loving kindness meditation (LKM) to mindfulness-based control (MC), each with chills augmentation (+) and without (−).ResultsAs hypothesized, LKM, compared to MC, increased connectedness to others, while chills augmentation to either stimulus (LKM+/MC+) enhanced ST, mood, emotional breakthrough, and psychological insight. Mediation analyses confirmed that the occurrence of aesthetic chills during meditation predicted these downstream effects. They also found trait measures that independently (of main effects) contributed to distinct outcomes: absorption predicted feelings of ego-dissolution, connectedness to the world and self, and moral elevation; interoceptive awareness predicted ego-dissolution and connectedness to self; and vividness of internal imagery predicted connectedness to the world and others.DiscussionChills augmentation appears a viable method for enhancing the immersiveness, salience, and downstream positive impact of guided contemplative interventions, without interfering with the intended outcome. This work can further our understanding of and access to non-ordinary experiences that beget salutogenic, prosocial outcomes.